(untitled) (Journal of the College of Basic Education, 2022)
Cohesion, the most important principle and criterion of textuality, is theconnection or the connectedness manifested when the interpretation of onetextual element, i.e., a word located in one sentence is dependent onanother element in the text. Cohesion is thus one of the text properties that contribute to theorganization of discourse. Coherence has to be clearly distinguished fromcohesion. Hence, cohesion refers to the overt semantic relations in the text,whereas coherence refers to semantic and pragmatic relations between theparts of the text. The three main categories of cohesion are referential cohesion(anaphoric chains), relational cohesion (connectives and ellipsis) andlexical cohesion. Lexical cohesion, which is the focus of this researchpaper, contributes to the ideational (semantic) structuring of discourse. Itrefers to the semantic relations between the lexical items in the text; thus itprovides information about the way lexemes are organized in the discourse. Lexical cohesion is the dependency relationship between wordsbased on associative relations in common knowledge. Lexical coherenceplays a dominant role in text structure. However, the lack of cohesion inwriting is a problem that plagues many EFL students. The present papergoal is to help students to overcome this problem in which it has been achallenge to EFL teachers and researchers alike. Thus, the present researchpaper aims at analyzing Kurdish EFL students’ emails for the purpose offinding out their tendency towards using lexical cohesion devices, i.e., theextent to which they use or avoid using these d